Prevalence of Thyroid Disorders in Type 2 Diabetes Mellitus Patients in Nepalgunj Medical College - Rahi, Altaban; Siddiqui, Saharoj; Mandal, Rajesh Kumar; Mikrani, Benazeer (Journal of Nepalgunj Medical College, 2024)
Introduction: Thyroid dysfunction is defined as the altered serum thyroid stimulation hormone level with normal or altered th roid hormones. It is a common endocrine disorder affecting around 300 million people worldwide. Hypothyroidism is a common thyroid disorder in diabetic patients, impacting diabetes control. Both thyroid dysfunction and diabetes are significant pub- lic health concerns in Nepal. Addressing thyroid dysfunction in diabetic patients is crucial for optimal disease management as untreated thyroid dysfunction can invariably affect glycemic control and contributes to cardiovascular complications. Aims: To assess the prevalence of thyroid disorders amongst Type 2 diabetic patients in Nepalgunj Medical College. Methods: This is a cross-sectional, hospital-based study conducted at the Diabetes Endocrine Outpatient Department, department of Medicine, and among indoor patients of these units at Nepalgunj Medical College. The study utilized a non-probability consecutive sampling technique. Results: Among the 100 participants, 37% had abnormal thyroid function whereas 63% of the participants had normal thyroid function. Among participants with diabetes over 13 years of duration 36.2% had thyroid dysfunction and with duration of diabetes 10-12 years 50% had thyroid dysfunction. The most common thyroid disorder present was subclinical hypothyroidism noted in 17% of the total participants. Conclusion: A high prevalence of thyroid dysfunction was seen in Type 2 Diabetes Mellitus patients. Screening for hypothyroidism, appropriate management and control of diabetes may lower the risk of thyroid dysfunction.